2021
DOI: 10.1002/slct.202102061
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Inhibitors with Cyclic Linker and Non‐hydroxamate Zinc Binding Group: Design, Synthesis, HDAC Screening and invitro Cytotoxicity evaluation.

Abstract: Recent evidences highlight the usefulness of small molecule (Histone deacetylase 4) HDAC4 inhibitors in the several preclinical paradigms. Major toxicity and mutagenicity issues associated with hydroxamate HDAC inhibitors, stimulated us to develop potent non-hydroxamate inhibitors. In the present work a novel series of thiazolidinedione (TZD) derivatives with pyridine as cyclic linker and TZD ring as zinc binding group was designed and screened in a panel of isoenzymes of HDACs, wherein the most potent compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The authors attributed the preference to bind HDAC4 to the carbonyl group of the TZD warhead. It was noted that previously described N-substituted TZD analogs were inactive, highlighting the importance of the NH group for HDAC4 selectivity [161]. Interestingly, compound 88 showed inhibitory activity of 750 nM and 12 µM toward HDAC4 and HDAC8, respectively, supporting prior studies suggesting a chelation of HDAC8 via the amide carbonyl.…”
Section: Thiazolidinedione (Tzd) Warheadssupporting
confidence: 62%
See 1 more Smart Citation
“…The authors attributed the preference to bind HDAC4 to the carbonyl group of the TZD warhead. It was noted that previously described N-substituted TZD analogs were inactive, highlighting the importance of the NH group for HDAC4 selectivity [161]. Interestingly, compound 88 showed inhibitory activity of 750 nM and 12 µM toward HDAC4 and HDAC8, respectively, supporting prior studies suggesting a chelation of HDAC8 via the amide carbonyl.…”
Section: Thiazolidinedione (Tzd) Warheadssupporting
confidence: 62%
“…Additional evaluation of 85 in CCRF-CEM tumor xenografts led to significant tumor regression [160]. Follow-up studies by Tilekar et al [161] identified TZD derivatives with a pyridine linker, replacing the naphthyl group. The most potent compound of the series 87 showed a potency of 4.9 µM toward HDAC4 and greater than 10-fold selectivity over HDAC8.…”
Section: Thiazolidinedione (Tzd) Warheadsmentioning
confidence: 99%
“…This study evaluated 223 TZD ligand analogs including newly synthesized compounds PB1-PB9 and GB1-GB36 with different substitution patterns (Table S1). Many of the TZD ligands have been published very recently to be HDAC4 or HDAC8 inhibitors [18,19,25]. This large ensemble of TZD ligands was utilized to derive a SAR and identify ligand moieties crucial for binding to the catalytic domain of human wild type histone deacetylase 4 (cdHDAC4 wt ).…”
Section: Chemistry Synthesis Of Compounds Pb1-pb9 and Gb1-gb36mentioning
confidence: 99%
“…Furthermore, some TZD ligands are capable to inhibit aldose reductase (ALR2), protein tyrosine phosphatase 1B (PTP1B) and α-glucosidase [18]. Very recently, we reported on TZD-containing ligands, which are capable to inhibit HDAC4 [18,19]. Enzyme activity assays of the HDAC family demonstrated activity of TZD ligands against HDAC4 or HDAC8 depending on the substitution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…incorporated a common pharmacophoric feature, which is a heterocyclic ring, "2,4-thiazolidinedione (TZD)" as a central or peripheral moiety that significantly contributed to antitumor activity by targeting single or multiple cancer hallmarks. [5][6][7][8][9][10][11][12][13][14][15] However, we also published compounds without the TZD nucleus showing good antiproliferative activity (Figure 1). [16][17][18][19][20][21][22][23][24][25] Interestingly, there are countless pieces of literature demonstrating compounds with anticancer activity incorporating various heterocyclic rings.…”
Section: Introductionmentioning
confidence: 96%